Uprising : how to build a brand--and change the world--by sparking cultural movements - Goodson, Scott (McGraw-Hill, 2012)
Movement marketing is changing the world. It's the new way forward for anyone trying to win customers' loyalty, influence public opinion, and even change the world. In Uprising, Scott Goodson, founder and CEO of StrawberryFrog, the world's first cultural movement agency, shows how your idea or organization can successfully ride this wave of cultural movements to authentically connect to the lives and passions of people everywhere. We are in the midst of a profound cultural transformation in which technology is making it easier than ever for anyone to share ideas, goals, and interests. Working with companies and brands ranging from SmartCar to Pampers to Jim Beam to India's Mahindra Group, StrawberryFrog and Goodson have led a paradigm focal shift away from one-on-one selling to sharing. Using client case studies and contributions from a global team of movement marketing forerunners-among them, political guru Mark McKinnon; Lee Clow, creative chief at TBWA/Chiat/Day; Apple evangelist Guy Kawasaki; and Marty Cooke, who helped make yellow LIVESTRONG bracelets synonymous with the fight against cancer-Goodson details why and how individuals and companies are embracing the movement phenomenon. He then applies these insights to practical steps that you can take right now to reach people through what matters most to them, including: Stop talking about yourself-let the movement control your message Home in on the core objectives of your concept or brand-and align these values with what people are for (or against) "Light the spark"--Create a culture within your organization that can embrace and drive a movement Leverage your assets-content, events, expertise, connecting platforms-to give people tools to spread your gospel Adjust concepts to travel across borders and link people across cultural boundaries.